Analysis of the Level of Physical Condition of Persis Solo U-20 Football Athletes in 2024 - Rimawan, Daniel Lindung; Ekawati, Febriani Fajar; Adi, Pomo Warih (Fair Play, 2025)
The physical condition of players is crucial for achieving maximum performance. This study aims to analyze the physical condition level of Persis Solo U20 players based on the physical tests that will be conducted. This research is a survey study with a descriptive design. The subjects of this study are all 25 football athletes of Persis Solo U20. The data collection technique uses a survey with a test instrument consisting of six test items: the 20-Meter Sprint Test (Speed), Arrowhead (Agility), Standing Long Jump (Power Strength), Push-Up (Strength), Sit-Up (Strength), and Yo-Yo Intermittent Recovery Level 2 (Endurance). The data analysis technique employs descriptive analysis with percentages based on classification norms, which are then processed into T-scores to determine the physical condition levels of Persis Solo U20 football athletes. The results of the descriptive statistical test show that. The speed component (Speed) has an average of 2.92, with most athletes (13 athletes or 52%) falling into the "excellent" category. The agility component (Agility) has an average of 16.98, with most athletes (13 athletes or 52%) in the "moderate" category. The explosive power component (Power Strength) has an average of 2.34, with most athletes (13 athletes or 52%) in the "poor" category. The abdominal muscle strength component (Strength) has an average of 57.4, with most athletes (21 athletes or 84%) in the "very poor" category.  The arm muscle strength component (Strength) has an average of 33.56, with most athletes (9 athletes or 36%) in the "very good" category. The endurance component (Endurance) has an average scale score of 20.26, with most athletes (9 athletes or 36%) in the "moderate" category. Overall, the physical condition has an average score of 301.772. Based on the classification norms, the physical condition falls into the "moderate" category, with most athletes (10 athletes or 40%) in this category.